Immunomodulation: Immunoglobulin Preparations Suppress Hyperinflammation in a COVID-19 Model via FcγRIIA and FcαRI - Bohländer, Fabian; Riehl, Dennis; Weißmüller, Sabrina; Gutscher, Marcus; Schüttrumpf, Jörg; Faust, Stefanie (Frontiers in Immunology, 2021)
The rapid spread of SARS-CoV-2 has induced a global pandemic. Severe forms of COVID-19 are characterized by dysregulated immune response and “cytokine storm”. The role of IgG and IgM antibodies in COVID-19 pathology is investigated quite well, whereas IgA is neglected. To improve clinical outcome of patients, immune modulatory drugs seem to be beneficial. Such drugs include intravenous immunoglobulin preparations, which were successfully tested in severe COVID-19 patients. Here we established a versatile in vitro model to study inflammatory as well as anti-inflammatory processes by therapeutic human immunoglobulins. We dissect the inflammatory activation on neutrophil-like HL60 cells, using an immune-complex consisting of latex beads coated with spike protein of SARS-CoV-2 and opsonized with specific immunoglobulins from convalescent plasma. Our data clarifies the role of Fc-receptor-dependent phagocytosis via IgA-FcαRI and IgG-FcγR for COVID-19 disease followed by cytokine release. We show that COVID-19 associated inflammation could be reduced by addition of human immunoglobulin preparations (IVIg and trimodulin). Whereby trimodulin elicits stronger immune modulation by more powerful ITAMi signaling. Besides IgG, the IgA component of trimodulin especially, is of functional relevance for immune modulation in this assay setup, highlighting the need to study IgA mediated immune response.